Case report: Rapid resolution of grade IV ICANS after first line intrathecal chemotherapy with methotrexate, cytarabine and dexamethasone - Katsin, Mikalai; Shman, Tatsiana; Migas, Alexandr; Lutskovich, Dzmitry; Serada, Yuliya; Khalankova, Yauheniya; Kostina, Yuliya; Dubovik, Simon (Frontiers in Immunology, 2024)
Corticosteroid therapy is the mainstay of immune effector cell-associated neurotoxicity syndrome (ICANS) management, although its use has been associated with worse overall survival (OS) and progression-free survival (PFS) after chimeric antigen receptor T-cell (CAR-T cell) therapy. Many options are being investigated for prophylaxis and management. Accumulating evidence supports the use of intrathecal (IT) chemotherapy for the management of high-grade ICANS. Here, we describe a case of a patient with stage IV Primary mediastinal B-cell lymphoma (PMBCL) successfully treated with IT methotrexate, cytarabine, and dexamethasone as first-line therapy for CD19 CAR-T cell-associated grade IV ICANS. The stable and rapid resolution of ICANS to grade 0 allowed us to discontinue systemic corticosteroid use, avoiding CAR-T cells ablation and ensuring preservation of CAR-T cell function. The described patient achieved a complete radiologic and clinical response to CD19 CAR-T cell therapy and remains disease-free after 9 months. This case demonstrates a promising example of how IT chemotherapy could be used as first-line treatment for the management of high-grade ICANS.